A Cause without a Rebel: The Rebranding of Forrest High School. (2nd November 2017) - Lee, Jason W.; Gregg, Elizabeth A.
Abstract : The public perception of academic institutions and their athletic programs are generally considered a prime factor in building their brand image. Maintaining a favorable institutional brand image can have a meaningful effect when conveying messages to key organizational stakeholders. Schools are to seek strategies aimed at generating positive exposure and conveying compelling messages that instill confidence in institutional stakeholders. For secondary schools, the ability to build and maintain a favorable brand image can be quite challenging. Accordingly, various factors can come into play regarding opportunities for building positive institutional brand associations and alleviating negative brand associations. This article addresses branding challenges that were experienced when a divisive school name and visible identity elements proved to be a contentious issue impacting the community. The process leading up to an institutional rebranding is presented, with specific attention to the significance of the strategic visual-identity planning process, including the implementation of the CHANGE model.